2021
DOI: 10.1155/2021/9930059
|View full text |Cite
|
Sign up to set email alerts
|

Surgery and Medical Treatment in Microprolactinoma: A Systematic Review and Meta-Analysis

Abstract: Objective. Dopamine agonists (DAs) are recommended as the first-line treatment for prolactinomas; however, tumour recurrence after drug withdrawal remains a clinical problem. Recent studies have reported high remission rates via surgery in microprolactinomas. The aim of this systematic review and meta-analysis was to compare the clinical result of DA treatment with surgery as initial therapy in patients with treatment-naive microprolactinoma. Methods. A comprehensive literature search for studies and reports r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…2). This updated Consensus Statement considers new evidence that has markedly influenced clinical practice, including incorporation of transcription factors into pituitary adenoma classification 3 , long-term adverse effects of dopamine agonist therapy 4 , outcomes following dopamine agonist withdrawal 5 and advances in surgical tumour resection [6][7][8][9] . In addition, management during pregnancy [10][11][12] , effects of hyperprolactinaemia on bone and fracture risk 13 , management of cystic and aggressive prolactinomas 14 , and prolactinomas in children and transgender patients are covered.…”
Section: Introductionmentioning
confidence: 99%
“…2). This updated Consensus Statement considers new evidence that has markedly influenced clinical practice, including incorporation of transcription factors into pituitary adenoma classification 3 , long-term adverse effects of dopamine agonist therapy 4 , outcomes following dopamine agonist withdrawal 5 and advances in surgical tumour resection [6][7][8][9] . In addition, management during pregnancy [10][11][12] , effects of hyperprolactinaemia on bone and fracture risk 13 , management of cystic and aggressive prolactinomas 14 , and prolactinomas in children and transgender patients are covered.…”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, most studies have reported higher remission rates for microprolactinomas compared to macroprolactinomas, and adenomas that are enclosed within the gland may have a more favourable outcome compared with adenomas located at the lateral margins [29,60]. These findings have been endorsed in several systematic reviews and meta-analyses, which have reported TSS to deliver superior clinical outcomes compared to dopamine agonist therapy [19,20,63], with superior costeffectiveness, although the absence of any randomised trials remains a major limitation [19]. Interestingly, one systematic review specifically investigated prolactinoma patients undergoing surgery because of resistance or intolerance to dopamine agonists, or patient preference, and reported that 38% achieved sustained remission without further treatment (66% of microprolactinomas, 22% of macroprolactinomas), while 62% achieved remission with adjunctive dopamine agonist therapy [64].…”
Section: Discussionmentioning
confidence: 97%
“…This should be distinguished from dopamine agonist resistance, which is preferred when there is failure to normalize serum prolactin and/or achieve significant tumor shrinkage (in macroprolactinomas) despite good tolerance and concordance with standard clinical dosages [17,18]. For patients with intolerance or resistance to medical therapy, transsphenoidal surgery (TSS) is an alternative treatment option [5], with several recent reports suggesting a higher long-term remission rate [19][20][21][22][23][24] and improved cost-effectiveness compared with dopamine agonist therapy [25,26]. As evidence for the efficacy and safety of transsphenoidal surgery (TSS) accrues, there is increasing discussion about the earlier deployment of surgery for selected cases [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with prolactinoma with drug intolerance or resistance, surgery is the next step in the treatment algorithm. Based on recent evidence, surgery is now increasingly considered as a first line treatment option for microprolactinomas and circumscribed macroprolactinomas in which complete resection can be anticipated [2,5,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. With more elective cases being considered for surgery, it becomes more clinically relevant to reliably identify the precise localization of the (remnant) lesion, possible multifocality, and its potential invasion in surrounding structures.…”
Section: Discussionmentioning
confidence: 99%